Obesity in Indian subjects with vascular dementia - Chandra, Mina; Anand, Kuljeet Singh (International Journal of Advances in Medicine, 2017)
Background: Obesity is considered a public health challenge in South Asia. Obesity is an independent risk factor in vascular dementia. It also contributes to other risk factors of vascular dementia like hypertension, coronary artery disease, dyslipidaemia and diabetes. As the rate of obesity in Indian subjects with vascular dementia is not known, we decided to assess obesity in subjects with vascular dementia. Methods: Subjects with vascular dementia presenting to Memory Clinic of a tertiary care hospital over a period of 16 months were assessed for body mass index as a marker of obesity and for severity of dementia. Data obtained was analysed using SPSS version 17. Results: Our study shows that in 159 subjects with vascular dementia about 17% subjects were overweight and 68% were obese. Only one subject was underweight. This is in excess of population prevalence of obesity in similar population. While there was no difference in age, education level and severity of dementia between subjects with normal weight, overweight and obesity, there was significant gender difference with females having more BMI than males in general and also across all levels of severity of dementia. This is in consonance with earlier studies showing female preponderance of obesity in subjects with vascular dementia. Conclusions: Obesity is common in subjects with vascular dementia especially in female subjects. As obesity is an important contributory factor in vascular dementia, it follows that obesity management must be included as a part of comprehensive management strategy in subjects with vascular dementia particularly in females.